The permanent crisis Iran's nuclear trajectory - Joshi, Shashank (Whitehall papers, 2012)
The first objective is to situate Iran's nuclear programme in the context of the security concerns of all of the interested parties, including Iran itself. The nuclear dispute is embedded in a set of overlapping security disputes between Iran on the one hand and the United States, Arab regional powers, Israel and the broader 'West' on the other. The second objective is to situate this examination of Iran in a comparative and thematic context. A large volume of information is available on, for instance, the historic efficacy of economic sanctions; on the influences that weigh upon states when deciding whether to pursue nuclear weapons; and on the ways in which states can and cannot use nuclear weapons as instruments of coercion or aggression. The third objective is to consider how policy responses by the West will and should evolve were Iran to resume its alleged nuclear-weapons programme, continue to undertake some degree of near-weaponisation or weaponisation or test and deploy nuclear weapons.